Competitiveness of Indonesian Footwear Commodities in the International Market - Avia Enggar Tyasti; Bayu Prabowo Sutjiatmo (Budapest International Research and Critics University, 2022)
This research was conducted to analyze the competitiveness of Indonesian footwear exports and to know the factors that influence footwear exports in 2013 to 2018. The data used are secondary data obtained from WITS, World Bank, UNCTAD. The analytical method uses Revealed Comparative Advantage (RCA) and Trade Specialization Index to determine the competitiveness, position of the Indonesian footwear market share, and regression analysis to analyze the factors that affect exports. The results of this study indicate that Indonesian footwear has comparative competitiveness, this is indicated by an RCA value > 1. Whereas based on the results of the analysis of Indonesian footwear Trade Specialization Index’s, the footwear product produced by Indonesia has a strong competitiveness and is included in the class of products that are already in the maturity stage with a value showing close to 1. The regression analysis results show that GDP per capita, population and volume exports have a significant and influence on the value of footwear exports.